Principal Interpersonal Communication in Decision Making And Policy Quality Improvement of MTs Ummi Lubuk Pakam - Hariyanto, Hariyanto; Wijaya, Candra; Y Yahfizham, Yahfizham; Zaini, Muhammad Fuad (CV. Inara, 2021)
The focus of the study is: 1) Communication interpersonal heads of madrassas in decision making and policy improvement of quality ; 2) Factors supporting the communication interpersonal heads of madrassas in the decision -making improvement of quality ; 3) obstacles head of madrassas in communication interpersonal pengamblan decisions and policies quality improvement . The formulation of the problem in this study is how the leadership of the headmaster of MTs Ummi Lubuk Pakam in improving the quality of students and the purpose of this study is to determine the leadership of the principal of MTs Ummi madrasah in improving the quality of students. This type of research this qualitative research and data collection techniques are observation, interview and documentation. The results showed that communication interpersonal heads of madrassas run by the well. Head madrassa raised an issue and discussed by listening to the input and output of the entire teachers and residents of the school are related. Head madrassa apply the value of the family to the entire citizens of the madrasa, so that citizens maadrasah feel dihaargai and dibutuhkaan so was born the attitude of loyalty that high directed toward madrasah and a sense of belonging madrasa good so kesdaran to improve the quality of madrasah is born of the whole wargaa madraasah it alone Making decisions that applied the head of the madrassa with a system of deliberation for the sake of generating results that best. Efforts to improve the quality of students who performed at the school by offering several programs -Program madarasah and extracurricular to grow skills and mentality of the participants students with the purpose of generating a graduate of the best of the value of the attitude and knowledge.